Determinants of climate change innovation in the wine industry: A study of meso and micro-level perspectives - Galbreath, Jeremy; Oczkowski, E. (ANZAM, 2013)
This study tests the drivers of climate change innovations in the wine industry. Taking a meso (cluster) and micro-level (firm) perspective, results of structural equation modelling analysis suggests that absorptive capacity (micro-level) is directly related to climate change innovations. Alternatively, absorptive capacity is directly related to knowledge exchange in the cluster (meso-level), which in turn is linked to climate change innovations. Hence, absorptive capacity has both direct and indirect effects. The study further finds that climate change innovations are related to firm performance and reductions in greenhouse gases: mitigative innovation impacts on greenhouse gas reductions while adaptive innovation impacts on firm performance. Implications of findings are discussed, along with future research directions and limitations.